A mioflora of Barren Measures age from the Auranga coalfield, Bihar - Lele, K.M.; Srivastava, A.K. (Journal of Palaeosciences, 1975)
The present paper describes for the first time a mioflora of Barren Measures age from the Auranga Coalfield. The assemblage (13 genera and 26 species) is dominated by striate-disaccates along with a good amount of Densipollenites. The quantitatively significant genera are Faunipollenites, Densipollenites, Striatites, Verticipollenites, Scheuringipollenites and Lahirites. Two species, Densipollenites brevis and Striatopodocarpites crassistriatus are new.